2022
DOI: 10.12703/r/11-6
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ regulation of constitutive vesicle trafficking

Abstract: Constitutive vesicle trafficking is the default pathway used by all cells for movement of intracellular cargoes between subcellular compartments and in and out of the cell. Classically, constitutive trafficking was thought to be continuous and unregulated, in contrast to regulated secretion, wherein vesicles are stored intracellularly until undergoing synchronous membrane fusion following a Ca 2+ signal. However, as shown in the literature reviewed here, many continuous trafficking steps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 135 publications
0
12
0
Order By: Relevance
“…Upon synthesis, the Na + /K + ATPase should translocate to the basal membrane to perform its functions properly. Rho kinase was shown to play a major role in the trafficking process [66], which is regulated by calcium and involves reorganization of the cytoskeleton [67,68].…”
Section: Discussionmentioning
confidence: 99%
“…Upon synthesis, the Na + /K + ATPase should translocate to the basal membrane to perform its functions properly. Rho kinase was shown to play a major role in the trafficking process [66], which is regulated by calcium and involves reorganization of the cytoskeleton [67,68].…”
Section: Discussionmentioning
confidence: 99%
“…Here, we will discuss their regulation by CaM. The main calcium stores in the mammalian cell are the ER, Golgi and the lysosome [ 31 ]. Calcium plays a well-established role in vesicle trafficking and CaM is emerging as an additional regulatory complex [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effectors of CaM that regulate endocytosis include calcineurin, a protein phosphatase, CaMKK2 and protein kinase C (PKC) [ 34–36 ]. Vesicle trafficking between the ER and Golgi is regulated by calcium through mechanisms that include Ca 2+ channels in the ER [ 31 ]. Vesicle formation is tightly regulated by the recruitment of membrane-binding and structural proteins that together form a coat of a defined size that envelope the membrane and create a bud that can be pinched off from the organelle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, it is believed to be a novel pan-neuronal calcium handling marker [ 7 ], associated with cancers [ 8 ], and stimulating insulin secretion [ 9 ]. According to the literature, NUCB1 protein is implicated in Alzheimer’s disease [ 10 , 11 ], other neurodegenerative diseases, or cellular processes known to be dysregulated early in tauopathy pathogenesis [ 12 ] such as synaptic plasticity, proteostasis, glucose metabolism, and mitochondrial function. Recently, a paper indicated that an adult-viable mutant that completely disrupts the G protein α-subunit binding and activates NUCB1 plays a neuroprotective role in the Drosophila model [ 13 ] of neurodegenerative disease.…”
Section: Introductionmentioning
confidence: 99%